2020
DOI: 10.1001/jamanetworkopen.2020.19843
|View full text |Cite
|
Sign up to set email alerts
|

Women Surgeons’ Experiences of Interprofessional Workplace Conflict

Abstract: IMPORTANCE Gender differences in interprofessional conflict may exist and precipitate differential achievement, wellness, and attrition in medicine. OBJECTIVE Although substantial attention and research has been directed toward improving gender equity in surgery and addressing overall physician wellness, research on the role of interprofessional conflict has been limited. The objective of this study was to understand scenarios driving interprofessional conflict involving women surgeons, the implications of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Similar to what has been published in other fields, 24‐26 women start without access to training in negotiation and information regarding salaries and other items that can be negotiated for starting contracts. As they advance their careers, they face pervasive systemic gender biases and power differentials that devalue their work, discount their accomplishments, and discourage assertive self‐advocacy, thus compounding their inability to achieve gender parity 8,11,27 . Thus, for the same level of productivity and achievement, women are systematically disadvantaged.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to what has been published in other fields, 24‐26 women start without access to training in negotiation and information regarding salaries and other items that can be negotiated for starting contracts. As they advance their careers, they face pervasive systemic gender biases and power differentials that devalue their work, discount their accomplishments, and discourage assertive self‐advocacy, thus compounding their inability to achieve gender parity 8,11,27 . Thus, for the same level of productivity and achievement, women are systematically disadvantaged.…”
Section: Discussionmentioning
confidence: 99%
“…Investigating women surgeons’ cross-occupational collaboration with nurses provides an excellent opportunity to explore gender and occupational status dynamics in cross-occupational collaboration because it represents an “extreme case,” even in medicine, of collaboration between women in male-dominated and female-dominated occupations. This examination thus increases the potential to observe the phenomenon of interest: whether and how women in male-dominated occupations face unique challenges and use unique response strategies in collaboration with women in female-dominated occupations (Eisenhardt, 1989; Dossett et al, 2020). Surgery has been considered the “last bastion of male-only medicine,” with only about one-fifth of surgeons being women (de Costa et al, 2018; Haskins, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have suggested several problems related to the careers of female surgeons.. Firstly, the lack of role models is often pointed out as a barrier to female surgeons’ careers,27 and female surgeons experience interprofessional conflict due to breakdowns in communication 28. Moreover, female surgeons find attaining leadership positions difficult 29…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the lack of role models is often pointed out as a barrier to female surgeons' careers, 27 and female surgeons experience interprofessional conflict due to breakdowns in communication. 28 Moreover, female surgeons find attaining leadership positions difficult. 29 Secondly, previous reports have shown a bias in the number of surgical cases assigned to male versus female surgeons during their training.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%